Cover Image. (7th June 2018) - Österlund, C.; Berglund, H.; Åkerman, M.; Nilsson, E.; Petersson, H.; Lam, J.; Alstergren, P.
Abstract : The cover image, by C. Österlund et al., is based on the Original Article Diagnostic criteria for temporomandibular disorders: Diagnostic accuracy for general dentistry procedure without mandatory commands regarding myalgia, arthralgia and headache attributed to temporomandibular disorder, DOI:10.1111/joor.12643 . Photo credit: Per Alstergren.